Emerging Intelligent Computing Technology and Applications. With Aspects of Artificial Intelligence 5th International Conference on Intelligent Computing, ICIC 2009 Ulsan, South Korea, September 16-19, 2009 Proceedings - Huang, De-Shuang; Jo, Kang-Hyun; Lee, Hong-Hee; Kang, Hee-Jun; Bevilacqua, Vitoantonio (Lecture Notes in Artificial Intelligence, 2009)
This book - in conjunction with the volume LNCS 5754 - constitutes the refereed proceedings of the 5th International Conference on Intelligent Computing, ICIC 2009, held in Ulsan, South Korea in September 2009. The 214 revised full papers of these two volumes were carefully reviewed and selected from a total of 1082 submissions. The papers of this volume are organized in topical sections on Neural Networks, Evolutionary Learning & Genetic Algorithms, Granular Computing & Rough Sets, Fuzzy Theory and Models, Fuzzy Systems and Soft Computing, Swarm Intelligence and Optimization, Supervised & Semi-supervised Learning, Kernel Methods and Supporting Vector Machines, Combinatorial & Numerical Optimization, Systems Biology and Computational Biology, Neural Computing and Optimization, Knowledge Discovery and Data Mining, Artificial Life and Artificial Immune Systems, Ensemble Methods, Machine Learning Theory and Methods, Biological and Quantum Computing, Intelligent Computing in Pattern Recognition, Dynamic Spectrum Sharing Systems, New Particle Swarm Optimization and Its Applications, Intelligent Signal Processing for Interactive Brain-Machine-Interfacing, Advances in Intelligent Information Processing, Computational Intelligence in Bioinformatics and Systems Biology, Network-based Intelligent Technologies, and 2D vs 3D Intelligent Biometric and Face Recognition Techniques.